Unburnt habitat patches are critical for survival and in situ population recovery in a small mammal after fire. Issue 6 (16th March 2021) - Shaw, Robyn E.; James, Alex I.; Tuft, Katherine; Legge, Sarah; Cary, Geoffrey J.; Peakall, Rod; Banks, Sam C.
Abstract: Fire drives animal population dynamics across many ecosystems. Yet, we still lack an understanding of how most species recover from fire and the effects of fire severity and patchiness on recovery processes. This information is crucial for fire‐mediated biodiversity conservation, particularly as fire regimes change globally. We conducted an experiment to test whether post‐fire recovery is driven by in situ survival or recolonisation, and to determine whether this varies with fires of increasing percentage area burnt (burn cover) and severity. We used the pale field rat Rattus tunneyi as a model, because it represents the extinction process for a suite of mammal species suffering population collapse across Australia's northern savannas. Our treatments spanned a gradient from patchy, low severity fires (simulating early dry season management burns) to thorough, high severity fires (simulating wildfires). We performed capture–mark–recapture, vegetation and aerial surveys before, 6 weeks after and 1 year after fire. Six weeks after fire, pale field rats were only captured in unburnt patches of vegetation, and capture rates were proportional to the amount of unburnt habitat. One year later, both vegetation and pale field rat populations recovered across all sites. However, population recovery after low severity fires was likely achieved through in situ survival and reproduction in unburnt micro‐refuges, compared to recolonisation driving recovery after high severity fires. Synthesis and applications . Pale field rat persistence is strongly dependent on the retention of unburnt habitat patches within fire‐affected areas. Management strategies that increase micro‐refugia within burnt areas may facilitate pale field rat population recovery. Globally, building recovery mechanisms into fire management will be vital for supporting the long‐term persistence of fire‐affected species. Abstract : Pale field rat persistence is strongly dependent on the retention of unburnt habitat patches within fire‐affected areas. Management strategies that increase micro‐refugia within burnt areas may facilitate pale field rat population recovery. Globally, building recovery mechanisms into fire management will be vital for supporting the long‐term persistence of fire‐affected species.